Dance steps as mnemonic device to increase retention rate of grade 7 students in chemistry (Southeast Asian Journal of Technology and Science, 2023)
The main purpose of this study is to determine the effect of using a new type of mnemonic device, utilizing dance steps in teaching Chemistry 7 in the retention rate of students on the properties of metals and non-metals. Different dance mnemonics corresponding to each property of the two types of elements were developed by the researcher. It was then utilized in teaching. The respondents of the study were the 91 grade 7 students of the two classes of the researcher in Science 7 during the first quarter of the S.Y. 2019-2020. Z-test was the statistical treatment used to compare the results of sample-experimental group to that of the population it was taken from. After utilizing the set of dance mnemonics developed corresponding to different properties of metals and non-metals, the samples performed better on the post-test compared to the population which means that using dance steps as mnemonic device increased the retention rate of grade 7 students. This study was limited only in the effect of using dance steps as a mnemonic device to increase the retention rate of grade 7 students in the properties of metals and non-metals.